PENYUSUNAN SPT TAHUNAN UMKM PASCA UU HPP - Dewanti, Yopy Ratna; Hermanto, Bambang; Utami, Rahayu Tri; Setiawan; Bakri (SEPAKAT Sesi Pengabdian pada Masyarakat, 2023)
Corporate Income Tax Return is a letter containing evidence of annual tax payments deposited by Corporate Taxpayers. Furthermore, proof of tax payment from the Income Tax Return must be reported to the Director General of Taxes. Then, the right alternative for reporting income tax returns is the Serpong tax consultant, because it is easier and more practical. The Annual Income Tax Return, hereinafter referred to as the Annual Income Tax Return, applies to a tax year or part of a tax year. The Annual Income Tax Return that must be reported annually or at the end of the tax year period is divided into two types, namely the Individual Annual Return (consisting of 3 types of forms) and the Corporate Return. Annual Income Tax Return (SPT) is a form used by taxpayers to report the calculation and / or payment of income tax, income tax objects, not income tax objects, assets and liabilities. As is known that the Tax Collection System in Indonesia uses the Self Assessment System where, the process of registering, calculating, paying and reporting Taxes is all done by the Taxpayer, so that taxpayers must report themselves to obtain an NPWP if they have met the objective and subjective requirements, taxpayers must calculate the tax to be paid in accordance with the taxpayer's business activities, taxpayers must pay the tax that should be paid by paying themselves to the State Treasury (through the Post Office or Perception Bank), and Tax Withholding / Collection by other parties and taxpayers must report all business activities in Periodic and Annual Tax Returns (SPT) according to actual conditions. For Corporate Income Tax Return must be reported at the latest on April 30th of the following tax year, so that taxpayers must immediately make and calculate their taxes from an early age, so that later there will be no errors in payment or reporting.